2014
DOI: 10.1111/mec.12804
|View full text |Cite
|
Sign up to set email alerts
|

Emergent patterns of population genetic structure for a coral reef community

Abstract: What shapes variation in genetic structure within a community of codistributed species is a central but difficult question for the field of population genetics. With a focus on the isolated coral reef ecosystem of the Hawaiian Archipelago, we assessed how life history traits influence population genetic structure for 35 reef animals. Despite the archipelago's stepping stone configuration, isolation by distance was the least common type of genetic structure, detected in four species. Regional structuring (i.e. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(128 citation statements)
references
References 72 publications
7
117
1
Order By: Relevance
“…The results clearly revealed the existence of a single panmictic population along the Brazilian coast ( sensu Selkoe et al)[87], and as reported by Vasconcellos et al [16], there is a high level of substructure between the Brazilian and Caribbean populations. However, it is worth mentioning that the absence of individuals sampled between Brazil and Belize makes it difficult to perform further analyses of the historical connectivity between populations in this geographic range.…”
Section: Discussionsupporting
confidence: 74%
“…The results clearly revealed the existence of a single panmictic population along the Brazilian coast ( sensu Selkoe et al)[87], and as reported by Vasconcellos et al [16], there is a high level of substructure between the Brazilian and Caribbean populations. However, it is worth mentioning that the absence of individuals sampled between Brazil and Belize makes it difficult to perform further analyses of the historical connectivity between populations in this geographic range.…”
Section: Discussionsupporting
confidence: 74%
“…While a link between dispersal ability and duration of the pelagic stage has considerable intuitive appeal, the relationship is not a simple one (Selkoe and Toonen, 2011;Selkoe et al, 2014). Nonetheless, fishes with a long pelagic larval stage tend to have extensive dispersal, broad ranges and dominate communities on isolated islands (Horne et al, 2008;Reece et al, 2011;.…”
Section: Is There Gene Flow From the Suture Zone Via Hybrid Offspring?mentioning
confidence: 99%
“…In addition, inherent reproductive characteristics of many marine species (e.g., pelagic larval duration [PLD], type of egg, spawning location) have been cited as factors that promote high levels of genetic connectivity among populations [2], even those separated by large geographic distances.…”
Section: Introductionmentioning
confidence: 99%